Penerapan Model Pembelajaran Project Based Learning Berbantuan Media Pembelajaran Scrapbook Terhadap Hasil Belajar - Fitri, Widia; Oknaryana, Oknaryana (Jurnal Ecogen, 2024)
This study aims to enhance learning outcomes for SMA Negeri 2 Batusangkar class XI.F6 students by using a scrapbook-based project-based learning paradigm. There are two cycles to this classroom action research project. There are two meetings in cycle I and two meetings in cycle II. Every cycle has four stages: preparation, execution, observation, and reflection. In the meantime, there are six learning processes in the project-based learning model: choosing the project, organizing the steps, creating a schedule, finishing the project, creating reports and presentations, and assessing the procedure. The results showed that improving student learning outcomes from cycle I to cycle II can be achieved with the scrapbook-assisted project-based learning paradigm. Student learning results in cycle I were 70.6%. At the second meeting, the percentage of students who completed their coursework increased to 88.2%.